2019
DOI: 10.1007/s00246-019-02185-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethnicity on the Prevalence of Early Repolarization Pattern in Children: Comparison Between Caucasian and African Populations

Abstract: The patterns and prevalence of early repolarization pattern (ER in paediatric populations from different ethnic backgrounds other than Caucasian have not been determined. Methods We analyzed ECGs of black children (ages xx-yy) who were prospectively recruited in the northwest Madagascar and compared them to age & sex matched Caucasian ethnicity individuals. ERP was defined by ≥0.1 mV J-point elevation in at least two contiguous inferior and/or lateral ECG leads. Results A total of 616 children were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…According to our pooled analyzed prevalence, ERP is approximately twice as common in blacks as in Caucasians, which is similar to previous studies [20,27,62] . Olson et al reported that 24.4% of blacks versus 7.9% of whites had J-point elevation based on Atherosclerosis Risk in Communities (ARIC) study [20,62] .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…According to our pooled analyzed prevalence, ERP is approximately twice as common in blacks as in Caucasians, which is similar to previous studies [20,27,62] . Olson et al reported that 24.4% of blacks versus 7.9% of whites had J-point elevation based on Atherosclerosis Risk in Communities (ARIC) study [20,62] .…”
Section: Discussionsupporting
confidence: 91%
“…[ 33 ] Six studies reported the prevalence in the Asia, including 3 in China [ 32 , 35 , 44 ] and 1 each in Japan, [ 8 ] Korea, [ 15 ] and Thailand. [ 34 ] Eight studies reported the prevalence in the United States [ 16 , 20 , 25 , 28 , 37 , 40 , 42 , 45 ] and 1 each study reported the prevalence in Madagascar, [ 27 ] Egypt, [ 29 ] and Latin America. [ 26 ] The worldwide prevalence map of ERP by region was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations